Effect of different types of acid-etching agents and adhesives on enamel discoloration during orthodontic treatment - Arman Mohmmadi Shayan; Ahmad Behroozian; Amirhouman Sadrhaghighi; Amirmohammad Dolatabadi; Sevda Hashemzadeh (Tabriz University of Medical Sciences, 2021)
Background. Acid etching and bonding is a routine process in orthodontic treatment. The present study aimed to evaluate enamel discoloration after using different types of acid etching and adhesive agents. Methods. A total of 105 extracted human premolars were divided into six groups regarding the type of acid etching agent: solution and gel of 37% phosphoric acid, and type of self-cured adhesive agent: Unite (3M, fluoride-free), Resilience (Ortho Technology), and Rely-a-Bond (Reliance, fluoride-releasing adhesive), with each group containing 15 specimens. All the selected teeth were subjected to a staining process, and color parameters were determined using a spectrophotometer. Results. The type of phosphoric acid (solution or gel) had no significant effect on the color change of enamel (P>0.05). Resilience significantly changed the enamel color compared to the Unite and Rely-a-Bond (P<0.001). There was no significant difference in color change between the Unite and Rely-a-Bond adhesives (P=0.67). The difference in color change between all the three time intervals (T0-T1, T1-T2, and T0-T2) was significant (P<0.001). Conclusion. In this study, the type of phosphoric acid (solution or gel) did not result in any significant difference in enamel color. Also, considering the lack of the effect of the orthodontic adhesive type in terms of fluoride release or no fluoride release, it can be concluded that this is most affected by the commercial brand of adhesives.